Chronic HIV Infection Impairs Nonopsonic Phagocytosis of Malaria Parasites. (1st February 2015) - Serghides, Lena; Finney, Constance A. M.; Ayi, Kodjo; Loutfy, Mona; Kain, Kevin C.
Abstract : Abstract: Malaria-specific immune responses are altered in HIV/malaria-coinfected individuals and are associated with higher parasite burdens and more severe clinical disease. Monocyte/macrophage phagocytosis is a major mechanism of malaria parasite clearance. We hypothesized that phagocytosis of malaria-parasitized erythrocytes is impaired in coinfected individuals and could contribute to the increased parasite burdens observed. We show that nonopsonic phagocytosis of Plasmodium falciparum parasitized erythrocytes is impaired in monocytes isolated from HIV-infected individuals. The observed defects in phagocytic capacity were rescued after 6 months of antiretroviral therapy, demonstrating the importance of HIV treatment and immune reconstitution in the context of coinfection. Abstract : Supplemental Digital Content is Available in the Text.